Modelos de la Estructura Electrónica de las Dendritas Neuronales - Reyes, A.; Galarraga, E.; Bargas, J. (Revista Mexicana de Ingenieria Biomedica, 1998)
In order to design artificial neuronal nets that posses a functional unit similar to a real neuron (“realistic”) it is required: a) the functional unit should possess the electrotonic structure of the real neuron, b) the functional unit should be able to develop the dynamics of the temporal firing patterns of the real neuron, and c) these firing patterns should be modulated [1]. This article classifies the passive models aimed to obtain the electrotonic structure of the neuron with dendrites and makes a bibliographic review of the most important articles on the topic. The passive modeling of neurons have two main goals: a) to obtain the electrotonic structure of neurons from experimental data (by fitting mathematical models to electrophysiological and anatomical data), and b) to model the electrotonic structure in order to simulate the passive behavior of neurons during the activation of synaptic inputs (computational models).